INFLUENCE OF RATIO MOLAR METHANOL ON MAKING BIODIESEL OF FISH OIL JAMBAL SIAM (Pangasius hypophthalmus) - Ismiana '; Edison '; N Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research aims to know the influence of ratio molar methanol on making biodiesel of fish oil Jambal Siam (Pangasius hypophthalmus). The method used is the molar ratio of experimental methods i.e. methanol 1:1, 1:1.5 and 1:2. The parameters tested were the chemical and physical characteristics, which function to determine the number of acid, number of saponification, number of ester, density, viscosity, and flash point. The research results showed the influence of the ratio of methanol-diesel oil yield of fish against Jambal Siam (Pangasius hypophthalmus) the most optimum is 1:2 with biodiesel yield of 94.67% and testing characteristics in accordance with SNI 04-7182-2006 i.e. acid number (mgKOH/g 0.309), numbers saponification (4.099 mgKOH/g), Esther (3.094 mgKOH/g), density 40oC (0.822 g/ml), kinematics viscosity 40oC (5.186 cSt), and flash point (137.67 oC).Keywords: Pangasius hypophthalmus, methanol, yield